Casa para a vida toda: Um lar para toda a vida: Em busca de uma linguagem atemporal na arquitetura - Cunha, Tatiane Vanessa Alves da (2022)
Architecture, seen as a mixture of art and science, follows humanity as one of its ancestral arts, fascinating the human being by the possibilities of modifying the environment, in order to make it adapted to the most diverse needs, seeking to combine functionality and beauty to the structures. Among the reasons that drove the investment of time and dedication to this work, regarding the chosen theme and the eternal admiration for Architecture, are the critical vision and a closer contact with problems and solutions focused on the Disability theme, which the author developed when working with the National Support Program for Health Care for People with Disabilities (PRONAS/PCD), of the Ministry of Health, in the role of analyst, gathering information and analyzes aimed at the effectiveness and effectiveness of the program, thus enabling the guidance of decision-making by managers. PRONAS/PCD has as one of its axes the incentive to actions and services developed by non-profit entities, associations and private foundations, which work in the field of people with disabilities. In addition, the pandemic scenario caused by the new corona virus (COVID-19) has brought enormous challenges to Public Health, which go beyond the critical phase of the disease and hospitalizations, passing through the cultivation of new habits and attitudes, which will possibly cause a change of behavior in the population creating a new market perspective. We are going through a major social reorganization where people have started to reevaluate these questions based on your real needs.